Protective Effects of Punicalagin on Caco-2 Intestine Cell Line under Oxidative Stress Caused by Tert-butyl hydroperoxide - Ulfat Omar,; Akram Aloqbi,; Marwa Yousr ,; Nazlin Howell, (Journal of Pharmacy and Nutrition Sciences, 2015)
Hydrolysable tannin polyphenols from pomegranate (punicalagin) have been reported to show a wide range of health properties correlated to their high antioxidant and free radical scavenging activities. The objective of the current study was to investigate the protective effect of punicalagin on cell viability and redox status of cultured Caco-2 cells exposed to oxidative stress induced by tert-butyl hydroperoxide. The production of malondialdehyde, and total glutathione levels, as well as the generation of reactive oxygen species were used as markers of cellular oxidative status. Pretreatment of Caco-2 cells with 5 and 10 µM punicalagin for 24 hours significantly protected cell viability after exposure to tert-butyl hydroperoxide IC50 = 3 mM for 2 hours. The examined doses prevented the decrease of total glutathione and the increase of malondialdehyde induced by tert-butyl hydroperoxide in Caco-2 cells. Reactive oxygen species generation provoked by tert-butyl hydroperoxide was significantly reduced at the same concnetrations. Finally, cell morphology with treatments before and after induction by tert-butyl hydroperoxide showed irreversible effect of the oxidizing agent. The results of the biomarkers analyzed showed that treatment of Caco-2 cells with the natural dietary antioxidant punicalagin protected the cells against oxidative stress.